Role of sphingolipid metabolites in the homeostasis of steroid hormones and the maintenance of testicular functions - Wang, Defan; Tang, Yedong; Wang, Zhengchao (Frontiers in Endocrinology, 2023)
With the acceleration of life pace and the increase of work pressure, the problem of male infertility has become a social problem of general concern. Sphingolipids are important regulators of many cellular processes like cell differentiation and apoptosis, which are ubiquitously expressed in all mammalian cells. Various sphingolipid catabolic enzymes can generate multiple sphingolipids like sphingosine-1-phosphate and sphingomyelin. Present studies have already demonstrated the role of steroid hormones in the physiological processes of reproduction and development through hypothalamus-pituitary-gonad axis, while recent researches also found not only sphingolipids can modulate steroid hormone secretion, but also steroid hormones can control sphingolipid metabolites, indicating the role of sphingolipid metabolites in the homeostasis of steroid hormones. Furthermore, sphingolipid metabolites not only contribute to the regulation of gametogenesis, but also mediate damage-induced germ apoptosis, implying the role of sphingolipid metabolites in the maintenance of testicular functions. Together, sphingolipid metabolites are involved in impaired gonadal function and infertility in males, and further understanding of these bioactive sphingolipids will help us develop new therapeutics for male infertility in the future.